Working with and Negotiating ‘Risk': Examining the Effects of Awareness Raising Interventions Designed to Prevent Child Sexual Exploitation - Weston, Samantha K. (The British journal of criminology, 2020)
This article considers the effects of an educational intervention with young people designed to reduce the risk of child sexual exploitation (CSE). Drawing on findings from a qualitative study, we consider processes of engagement with the initiative, the relevance of the strategy adopted by the delivery team and the impacts on the perspectives of young people targeted. Focusing on mutually constitutive problems of context sensitivity, recognition of ambiguity and the silencing of alternative narratives, we raise several critical caveats that should be considered in the design and implementation of future CSE awareness raising initiatives. Overall, we aver that an unstinting focus on individual behaviour management unduly responsibilizes young people and draws inflexible demarcation lines between appropriate and inappropriate sexual conduct.